Towards no incisional hernias: lateral paramedian versus midline incisions. - Cox, P J (1986)
A prospective randomized controlled clinical trial is reported which compares midline with lateral paramedian incisions in relation to the development of incisional hernias at one year. Of 431 patients randomized, 329 were available for assessment one year later. Two patients suffered burst abdomen, both being in the lateral paramedian group. Twenty-two incisional hernias occurred, 2 in the lateral paramedian group and 20 in the midline group (P less than 0.001). Of the two types of incision, the lateral paramedian incision takes longer to perform, requires a longer incision, rarely results in dehiscence, and does confer protection against incisional hernia.